Glymphatic-assisted perivascular brain delivery of intrathecal small gold nanoparticles - Lilius, Tuomas O.; Mortensen, Kristian Nygaard; Deville, Claire; Lohela, Terhi J.; Stæger, Frederik Filip; Sigurdsson, Björn; Fiordaliso, Elisabetta M.; Rosenholm, Marko; Kamphuis, Chris; Beekman, Freek J.; Jensen, Andreas I.; Nedergaard, Maiken (Elsevier, 2023)
Nanoparticles are ultrafine particulate matter having considerable potential for treatment of central nervous system (CNS) disorders. Despite their tiny size, the blood-brain barrier (BBB) restricts their access to the CNS. Their direct cerebrospinal fluid (CSF) administration bypasses the BBB endothelium, but still fails to give adequate brain uptake. We present a novel approach for efficient CNS delivery of 111In-radiolabelled gold nanoparticles (AuNPs; 10–15 nm) via intra-cisterna magna administration, with tracking by SPECT imaging. To accelerate CSF brain influx, we administered AuNPs intracisternally in conjunction with systemic hypertonic saline, which dramatically increased the parenchymal AuNP uptake, especially in deep brain regions. AuNPs entered the CNS along periarterial spaces as visualized by MRI of gadolinium-labelled AuNPs and were cleared from brain within 24 h and excreted through the kidneys. Thus, the glymphatic-assisted perivascular network augment by systemic hypertonic saline is a pathway for highly efficient brain-wide distribution of small AuNPs.
Keywords: Central nervous system drug delivery; Glymphatic system; Hypertonic solution; Nanoparticles; Single-photon emission tomography; Pharmaceutical Science